Development of soft skills as a factor of improving the efficiency of social workers - Бутиліна, О. В.; Радченко, Н. Р. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2020)
The article analyzes soft skills as a group of "soft" over-professional skills that have a strong impact on the nature of the specialist’s interaction with his environment. The importance of developing these qualities among social workers is emphasized. It is noted that the system of vocational training and training of future specialists does not provide for the formation of "soft" competencies. The authors see the development of soft skills of social workers as a management task. There are two areas of work with staff, which are focused on the development of soft skills. The first is an active supervisory experience as learning from the experience of others (working with a mentor). It is emphasized that such a supervision is a tool for the formation of "soft" qualities of specialists and prevents the occurrence of stressful conditions. The second is the development of staff by updating, replenishing and improving the knowledge, skills and abilities of specialists. The authors propose specific management methods in accordance with the allocated areas: 1) the elaboration of individual development plans for employees; 2) search and accounting of feedback; 3) the involvement of experienced employees in the supervision implementation; 4) rotation of personnel; 5) the creation of a moral and psychological climate in the team, which stimulates self-development and self-education of employees. The article concludes that it is difficult to evaluate the degree of development of over-professional skills. The need to develop soft skills among social workers as a condition for improving the quality of their services is proved. Promising areas of research on the problem are being identified: opportunities to modernize the training system and develop a management strategy to take into account the development of soft skills of employees; creating a methodology for assessing and measuring the level of development of the "soft" competences of social workers at different stages of their professional careers.